Three 3D graphics engineering technologies for fallow deer antlers characterization in ecology and management approaches - Juan Manuel Montalvo-Gil; Concepción Azorit; Diego Francisco García-Molina; José Manuel Valderrama-Zafra; Miguel Ángel Rubio-Paramio (Discover Applied Sciences)
Abstract Numerous studies focus on creating 3D-models of biological elements for geometric evaluation using CAD tools. A crucial aspect is to obtain accurate geometrical data that is easy to obtain and cost-effective for analysis. The main objective is to evaluate the geometrical accuracy of 3D-models obtained with three graphical techniques of three-dimensional geometrical documentation that characterise the fallow deer antlers in an accurate 3D-model, which is used as input data in biological analyses estimating hunting quality, asymmetry and volume. Three technologies are evaluated: structured light scanning, multi-image photogrammetry (SfM), Structure from Motion, and spatial photogrammetric restitution using two photographs in a CAD system. The geometric accuracy of the 3D-models obtained and the deviation between relevant points of the antler structure, in the main beam, in the main tines and palm, are estimated. Subsequently, the suitability of each 3D-model is studied according to the type of biological application for which it is intended. Based on the results, solid and axial 3D-models, the applicability of the three techniques for the study of biological parameters such as hunting quality, asymmetry and volume is discussed. It concludes on the most appropriate procedure to define the digital characterisation of the antler, depending on the type of biological study to be carried out in order to obtain accurate results. Characterising a geometrically complex structure such as the fallow deer antler in a 3D-model quickly and accurately can help to quantify various biomarkers in populations of specimens, making it possible to infer internal and external influencing factors.